2018
DOI: 10.3389/fimmu.2018.02912
|View full text |Cite
|
Sign up to set email alerts
|

Current Understanding and Future Research Priorities in Malignancy Associated With Inborn Errors of Immunity and DNA Repair Disorders: The Perspective of an Interdisciplinary Working Group

Abstract: Patients with inborn errors of immunity or DNA repair defects are at significant risk of developing malignancy and this complication of their underlying condition represents a substantial cause of morbidity and mortality. Whilst this risk is increasingly well-recognized, our understanding of the causative mechanisms remains incomplete. Diagnosing cancer is challenging in the presence of underlying co-morbidities and frequently other inflammatory and lymphoproliferative processes. We lack a structured approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…The introduction of newborn screening for SCID will detect a number of these diseases, meaning that an accurate and speedy genetic diagnosis is imperative in order to define the most appropriate treatment regimen. Furthermore, the high incidence of lymphoid malignancies in these diseases should alert clinicians treating oncology patients to the possibility of an underlying systemic DNA repair disorder indicative of primary immunodeficiency [ 100 ], prior to embarking on treatment, to minimize treatment-related toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of newborn screening for SCID will detect a number of these diseases, meaning that an accurate and speedy genetic diagnosis is imperative in order to define the most appropriate treatment regimen. Furthermore, the high incidence of lymphoid malignancies in these diseases should alert clinicians treating oncology patients to the possibility of an underlying systemic DNA repair disorder indicative of primary immunodeficiency [ 100 ], prior to embarking on treatment, to minimize treatment-related toxicities.…”
Section: Discussionmentioning
confidence: 99%
“…It can lead to skin or visceral granulomatous lesions driven in some circumstances by persistent chronic infections such as vaccine-derived rubella virus (3). Increased susceptibility to malignancies, particularly lymphoma is observed (4). This can be due to impaired immunosurveillance to viral or tumoral antigens; chronic inflammation and infection with oncogenic viruses such as Epstein Barr Virus (EBV) can also promote lymphoproliferation.…”
Section: Heterogeneity Of Combined Immunodeficienciesmentioning
confidence: 99%
“…During food challenges, we found that lipid-rich mammalian meats were associated with more consistent, severe reactions. 2 Thus, we hypothesized that glycolipid could activate allergic effector cells in alpha-gal allergy. A role for lipids in enhancing allergenic potency has been described in peach 3 and cow's milk allergies.…”
Section: Glycolipid-mediated Basophil Activation In Alpha-gal Allergymentioning
confidence: 99%